The Effect of Academic Progression on EFL Learning Self-Efficacy among English Education Students in an Indonesian University - Marshanda Marshanda; Raysha Ramadhani; Rica Amelia Putri; Nazila Rahmadana; Abdul Syahid (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the effect of academic progression on EFL learning self-efficacy among English Education students at a state university in Indonesia. Although self-efficacy has been widely recognized as a key factor influencing learners’ motivation, engagement, and academic performance, limited research in the Indonesian context has explored whether confidence levels differ meaningfully across academic stages. To address this gap, the study compared the self-efficacy of second-year and third-year students using a quantitative comparative design. A total of 30 participants completed a validated Academic Self-Efficacy Scale, and the data were analyzed using descriptive statistics, reliability testing, assumption checks, and independent samples t-tests. The results showed that both groups demonstrated moderately high self-efficacy, with third-year students reporting slightly higher scores; however, the difference was not statistically significant. These findings suggest that academic progression alone may not substantially influence learners’ self-efficacy when instructional conditions and learning experiences remain relatively similar. The study highlights the need for providing meaningful mastery experiences and supportive pedagogical practices to strengthen self-efficacy development across students’ academic journeys in Indonesian higher education.